DEFORESTASI SEBAGAI PELANGGARAN FIQH ALBI’AH PERSPEKTIF YUSUF AL-QARADAWI - Saipul Nasution; Muhammad Azrul Amirullah; ‘Ilma Tsaqila Khoirun Nisa; Andini Rachmawati (MIYAH: Jurnal Studi Islam, 2026)
This study aims to analyze the phenomenon of unemployment from the perspective of human resource development based on Islamic values, specifically through the maqasid al-shari’ah approach. Conventional development models focused solely on economic growth often fail to comprehensively address unemployment issues because they neglect the dimensions of ethics, social justice, and spirituality. This study employs a qualitative method using a literature review approach, examining various classical and contemporary works related to Islamic economics and human development. The findings indicate that unemployment is not merely an economic issue but also reflects a failure in the holistic management of human resources. From the perspective of the maqasid al-shari’ah, development must be directed toward the protection of religion, life, intellect, lineage, and wealth, which implicitly demands the creation of fair, productive, and dignified employment opportunities. Therefore, a reconstruction of development policies is necessary one that focuses not only on macroeconomic indicators but also on the comprehensive enhancement of human quality. This study is expected to provide a conceptual contribution to the development of public policies based on Islamic values to address unemployment in a sustainable manner.